Multiple apocrine hydrocystomas in feline: intralesional application of 20% trichloroacetic acid - case report - B.B. Vaz; F.S. Flores; F. I. Farencena; L.F.D. Corrêa (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Hidrocystomas are well-defined, firm to fluctuant, pigmented nodules measuring 2 to 10mm in diameter. They develop on both the upper and lower eyelids and may be located at the medial and/or lateral canthi of the eyelids. Classified as a benign tumor, its origin may derive from apocrine sweat glands such as the glands of Moll. The definitive diagnosis occurs through histopathological analysis. The objective was to report a case of multiple apocrine hidrocystomas in a feline treated with intralesional injection of 20% trichloroacetic acid (TCA). A 12-year-old Persian feline, with a history of blackish-colored nodules on the palpebral fissure of both eyes, which had already been removed by excision surgery and had recurred, was treated. Clinical suspicion of apocrine hidrocystoma was raised based on the patient’s history. The surgical removal of a nodule for histopathological analysis and the application of 20% TCA to the remaining nodules were recommended. The patient was discharged 21 days after the surgical procedure with full recovery. Hidrocystomas may present recurrences when treated only with surgical excision. However, the application of 20% TCA presented satisfactory results in the total remission of these neoplasms and kept the patient stable without signs of recurrence for 12 months of monitoring.